2023
DOI: 10.3390/nu15143079
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Inflammation Is Associated with Food Intake in Hospitalized Geriatric Patients—A Merged Data Analysis

Abstract: The extent to which inflammation impacts food intake remains unclear, serving as a key risk factor for malnutrition as defined by the Global Leadership Initiative on Malnutrition (GLIM). To address this, we analyzed a large, merged dataset of geriatric hospitalized patients across Europe. The study included 1650 consecutive patients aged ≥65 year from Germany, Italy, Finland, Denmark, and Poland. Nutritional intake was assessed using the first item of the Mini Nutritional Assessment Short Form; C-reactive prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…These thresholds are provided to help support identification of individuals with inflammatory diseases and conditions, not to assess risk for development of disease. They are consistent with reports that moderate and severe inflammation may be associated with significant reductions in food intake in hospitalized older patients 33 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These thresholds are provided to help support identification of individuals with inflammatory diseases and conditions, not to assess risk for development of disease. They are consistent with reports that moderate and severe inflammation may be associated with significant reductions in food intake in hospitalized older patients 33 …”
Section: Resultssupporting
confidence: 93%
“…Many of these publications were disease‐ or setting‐specific—for example, end‐stage renal disease or critical care. However, a more general analysis of a merged data set of geriatric hospitalized patients from across Europe 33 found that food intake was more likely to be significantly compromised at CRP levels above 30 mg/L. Therefore, little guidance was available in the context of the more general application to malnutrition diagnosis sought by GLIM, such that extrapolation of established inflammation assessments from other specific medical conditions proved necessary.…”
Section: Methodsmentioning
confidence: 99%